Effects of Heliox in Stable COPD Patients at Rest and during Exercise - Matteo Pecchiari (Pulmonary Medicine)
Heliox has been administered to stable chronic obstructive pulmonary disease (COPD) patients at rest and during exercise on the assumption that this low density mixture would have reduced work of breathing, dynamic hyperinflation, and, consequently, dyspnea sensation. Contrary to these expectations, beneficial effects of heliox in these patients at rest have been reported only sporadically, and the majority of the studies performed until now suggests that heliox is not a therapeutic option in spontaneously breathing resting COPD patients. On the other hand, when it is administered to COPD patients exercising at a constant work rate, heliox systematically decreases dyspnea sensation, and, often but not always, increases exercise tolerance. For these reasons, heliox has been evaluated as a non pharmacological tool to power rehabilitation programs. The conflicting results provided by the published trials probably point at a substantial heterogeneity of the COPD patients population in terms of respiratory mechanics and gas exchange. Therefore, further studies, aimed to the identification of mechanisms conditioning the response of exercising COPD patients to heliox, are warranted, before heliox administration, which is costly and cumbersome, can be routinely used in rehabilitation programs.